The woman from Tantoura - ʻĀshūr, Raḍwá (Hoopoe, an imprint of American University in Cairo Press, 2019)
"Ruqayya was only thirteen when the Nakba came to her village in Palestine in 1948. The massacre in Tantoura drove her from her home and from everything she had ever known. She had not left her village before, but she would never return. Now an old woman, Ruqayya looks back on a long life in exile, one that has taken her to Syria, Lebanon, the Gulf, and given her children and grandchildren. Through her depth of experience and her indomitable spirit, we live her love of her land, her family, and her people, and we feel the repeated pain of loss and of diaspora."--Publisher description